ANALISIS IMPLEMENTASI PEMBELAJARAN VOKASIONAL UNTUK ANAK BERKEBUTUHAN KHSUS DI SLB NEGERI TAMANSARI - Nisaa, Syahla Hulwatun; Asmiati, Neti; Mulia, Dedi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the suboptimal implementation of vocational learning for students with special needs at SLB Negeri Tamansari in supporting students’ independence and work readiness. The study aims to analyze the implementation of vocational learning based on educational management functions, including planning, organizing, implementation, and supervision. This research employs a descriptive qualitative method with data collection techniques consisting of observation, interviews, and documentation. Data analysis uses the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing, supported by triangulation to ensure data validity. The findings reveal that vocational program planning is based on students’ needs assessment and adaptive curriculum, but lacks competency testing standards and adequate facilities. Organizational aspects involve collaboration among schools, teachers, parents, and industry partners, although not yet optimal. The implementation is conducted through demonstrations, hands-on practice, and work habituation, yet faces challenges such as varying student abilities and limited resources. Supervision is carried out through evaluation of learning processes and outcomes, but lacks a comprehensive monitoring system. The study implies the need to strengthen vocational program management through improving teacher competence, developing infrastructure, establishing competency-based evaluation standards, and expanding partnerships to enhance the independence and work readiness of students with special needs.